IMPLEMENTASI MODEL ABC PADA RUMAH SAKIT DENGAN MENGGUNAKAN METODE QFD DAN BENCHMARKING: CONTOH DESAIN - Rini Oktavera (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
This research applied quality function deployment method and benchmarking to find outcustomer needs (a hospital) in term of problems relating with ABC based-costinformation system (ABC system) in a hospital. QFD and benchmarking approach wasused to yield an ABC model based on technical response which is identified from VOC(voice of customer) analysis. Collected information is not only for determining accurateproduct cost but it is also useful for operational strategic related with processimprovement, product design and performance measurement.First step is to identify customer needs (a hospital) toward activity based informationsystem (ABC system). Next step is to determine customer needs’ priorities based on thecollected questionnaire. Best activity is found after constructing matrix of a technicalresponse from a hospital against customer needs. Further step is to do competitor’sbenchmarking analysis to obtain hospital condition against its competitor. Thisinformation will be useful for making an improvement plan toward its own currentactivity based-information system.Analysis result shows that customer needs toward ABC model is detail cost informationper patient for administration item. Meanwhile, technical response considered byhospital to have high sensitivity toward ABC model is labor cost, special treatment cost,material cost (medicines), laboratory services, material cost for treatment